Activation of metabolite receptor GPR91 promotes platelet aggregation and transcellular biosynthesis of leukotriene C4. (17th February 2020) - Tang, Xiao; Fuchs, David; Tan, Shuai; Trauelsen, Mette; Schwartz, Thue W.; Wheelock, Craig E.; Li, Nailin; Haeggström, Jesper Z.
Abstract: Background: Succinate is a Krebs cycle intermediate whose formation is enhanced under metabolic stress, and for which a selective sensor GPR91 has been identified on various cell types including platelets. Platelet‐derived eicosanoids play pivotal roles in platelet activation/aggregation, which is key to thrombus formation and progression of atherothrombosis. Objectives: This study aims to decipher the molecular mechanism(s) and potential involvement of eicosanoids in succinate enhanced platelet activation/aggregation. Methods: We used liquid chromatography‐mass spectrometry (LC‐MS)/MS‐based lipid mediator profiling to identify eicosanoids regulated by succinate. We ran light transmittance aggregometry and flow cytometry to assess platelet aggregation, P‐selectin expression, and platelet‐polymorphonuclear leukocyte (PMN) adherence. Various pharmacological tools were used to assess the contributions of GPR91 signalling and eicosanoids in platelet aggregation. Results: Succinate and two types of synthetic non‐metabolite GPR91 agonists— cis ‐epoxysuccinate (cES) and Cmpd131—potentiated platelet aggregation, which was partially blocked by a selective GPR91 antagonist XT1. GPR91 activation increased production of 12‐hydroxy‐eicosatetraenoic acid (12‐HETE), thromboxane (TX) A2, and 12‐hydroxy‐heptadecatrienoic acid (12‐HHT) in human platelets, associated with phosphorylation of cytosolic phospholipase A2 (cPLA2 ), suggesting increased availability of free arachidonic acid. Blocking 12‐HETE and TXA2 synthesis, or antagonism of the TXA2 receptor, significantly reduced platelet aggregation enhanced by GPR91 signalling. Moreover, platelet‐PMN suspensions challenged with succinate exhibited enhanced transcellular biosynthesis of leukotriene C4 (LTC4 ), a powerful proinflammatory vascular spasmogen. Conclusion: Succinate signals through GPR91 to promote biosynthesis of eicosanoids, which contribute to platelet aggregation/activation and potentially vascular inflammation. Hence, GPR91 may be a suitable target for pharmacological intervention in atherothrombotic conditions.